2017
DOI: 10.3390/fermentation3040055
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GR-1 in Fermented Rice Pudding Supplemented with Short Chain Inulin, Long Chain Inulin, and Oat as a Novel Functional Food

Abstract: Lactobacillus rhamnosus GR-1 is a probiotic that has been shown to reduce the risk of urogenital problems and urinary tract infections. Rice pudding is a popular gluten-free dairy product, and could be a vehicle to deliver L. rhamnosus GR-1 to a broader population. The purpose of this study was to investigate the growth and viability of L. rhamnosus GR-1 in six fermented rice pudding samples, each one supplemented with one type of prebiotic (short-chain inulin-2% w/w, 4% w/w; long-chain inulin-2% w/w, 4% w/w) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…The results of Treatments 2-4 were comparable to that of the control (Treatment 1), thereby exhibiting the incorporation of soymilk and durations of fermentation and storage did not induce a loss in bacterial viability. Previous studies also demonstrated successful inoculation of L. rhamnosus GR-1 in non-dairy matrices, such as fruit and vegetable juices and fermented rice pudding to determine their suitability as carriers of probiotics [24,25,29,30]. Mean viable microbial loads of at least 10 7 -10 9 CFU/mL were reached in all cases [24,25,29,30].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results of Treatments 2-4 were comparable to that of the control (Treatment 1), thereby exhibiting the incorporation of soymilk and durations of fermentation and storage did not induce a loss in bacterial viability. Previous studies also demonstrated successful inoculation of L. rhamnosus GR-1 in non-dairy matrices, such as fruit and vegetable juices and fermented rice pudding to determine their suitability as carriers of probiotics [24,25,29,30]. Mean viable microbial loads of at least 10 7 -10 9 CFU/mL were reached in all cases [24,25,29,30].…”
Section: Discussionmentioning
confidence: 78%
“…Each treatment was heated in a water bath, held at a temperature of 85-87 • C for 30 min, and cooled to 40 • C. Thereafter, 3% (w/v) plain yogurt starter culture (2% milk fat) (Astro ® Original Balkan Yogourt, Plain, No Gelatin, Parmalat Canada Inc., Toronto, ON, Canada) from Sobeys, London, ON, Canada and 4% (w/v) probiotic mother culture were inoculated in each sample under aseptic conditions and stirred well. This probiotic culture concentration has been used in previous studies [24,25]. Each treatment was distributed into eight, 30 mL beakers.…”
Section: Fermentation and Storage Of Probiotic Yogurtmentioning
confidence: 99%
“…In our study, we found that there was no effect on the growth and viability of L. rhamnosus GR-1 when short chain and long chain inulin fiber was added. However, other studies have shown that the addition of inulin fiber increases cell viability in yogurt [30,37]. The work of Nikmaram et al, added inulin fiber to pomegranate juice supplemented with yogurt, and found that the survival of L. casei was increased [38].…”
Section: Discussionmentioning
confidence: 99%
“…The juices were cooled to 37 • C, subsequently 3.75% (w/v) of the stock culture containing L. rhamnosus GR-1 was added. The bacterial load was based on the percent inoculum which is the method used in other published studies [37]. The juices were covered and gently swirled to ensure the contents were well-mixed.…”
Section: Fruit Juice Fermentationmentioning
confidence: 99%
“…rhamnosus is a further species commercially exploited for the manufacture of fermented foods with healthy properties, given its high potential as a probiotic [ 45 , 46 ]. In recent years, this microorganism has been detected in a rice-based product (rice pudding) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%